2019
DOI: 10.1111/trf.15432
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus prevalence and incidence estimates among Chinese blood donors

Abstract: were screened in parallel by two different enzyme-linked immunosorbent assays for anti-HIV 1/2, hepatitis B surface antigen, anti-HCV, and syphilis. Screeningreactive samples were further confirmed by western blot. Confirmatory positive rates among first-time and repeat donors were used to estimate the prevalence and incidence rates. Multivariable logistic regression modeling was used to examine factors associated with HCV infection. RESULTS:A total of 1,276,544 donations were collected from five Chinese blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
5
1
1
Order By: Relevance
“…Here, we showed a significant difference in the serum anti-HCV-positive rate among different age groups, which increased with increasing age and was significantly higher in patients older than 40 years than in those below 40 years old. This result is consistent with previous studies [18,27,28] indicating that the infection rate of HCV in younger people is reducing, which is attributed to the increasingly more strict and standardized inspection and management of blood and blood products [29]. Moreover, there was an interaction between age and sex in that there was no sex difference in anti-HCVpositive prevalence among patients younger than 20 years, whereas males had a higher prevalence in patients older than 20 years.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we showed a significant difference in the serum anti-HCV-positive rate among different age groups, which increased with increasing age and was significantly higher in patients older than 40 years than in those below 40 years old. This result is consistent with previous studies [18,27,28] indicating that the infection rate of HCV in younger people is reducing, which is attributed to the increasingly more strict and standardized inspection and management of blood and blood products [29]. Moreover, there was an interaction between age and sex in that there was no sex difference in anti-HCVpositive prevalence among patients younger than 20 years, whereas males had a higher prevalence in patients older than 20 years.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, our analysis demonstrated that only an advanced age was independently associated to increased risk of CHB/CHC (OR = 1.05); it is possible that surgery performed before the diffusion of presurgical hepatitis screening could explain this result, and the fact that CHC were more common in subjects operated before 1990 could be a confirmatory finding. Indeed, the introduction of the HBV vaccine and HCV routine detection allowed an improvement in the prevention measures against viral hepatitis transmission during surgery or blood donation, thus reducing the risk of infection in young generations [ 18 ]. As expected, vaccinated patients were younger than non-vaccinated ones, and this may be another possible explanation of our result.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transmission is another major route of HCV infection, with a prevalence of 166.56 per 100,000 among first-time blood donors and 15.21 per 100,000 among regular blood donors ( Fu et al, 2019 ). The prevalence of hepatitis C in hemodialysis patients was approximately 10%, which is higher than the general population ( Jadoul et al, 2019 ).…”
Section: Epidemiological Characteristics Of Hepatitis C In the Mainla...mentioning
confidence: 99%